Biotin: a scoping review for Nordic Nutrition Recommendations 2023 - Beate Stokke Solvik; Tor A. Strand (Food & Nutrition Research, 2024)
Biotin is a water-soluble B-vitamin with key roles in metabolism and are found in most foods at low concentrations. Symptomatic biotin deficiency is rare, and few studies have investigated biotin requirements in relation to health outcomes. Data to support the setting of dietary reference values for biotin are limited.